Fe-doped Beta zeolite from organotemplate-free synthesis for NH3-SCR of NOx. Issue 17 (1st July 2016) - Zhu, Yongjun; Chen, Bingbing; Zhao, Rongrong; Zhao, Qi; Gies, Hermann; Xiao, Feng-Shou; De Vos, Dirk; Yokoi, Toshiyuki; Bao, Xinhe; Kolb, Ute; Feyen, Mathias; Maurer, Stefan; et al.
Abstract : Structure–performance correlations suggest that the content of isolated Fe 3+ in the Beta zeolite affects the SCR activity directly. Abstract : Two types of Beta zeolites, one from organotemplate-free synthesis with a Si/Al ratio of 9 and the other from a commercial one with a Si/Al ratio of 19, were employed here to dope Fe for NH3 -SCR of NO x . Fe-Beta (Si/Al = 9) exhibits much higher activity than Fe-Beta (Si/Al = 19), especially at low-temperature regions (<250 °C). In addition, it also exhibits better hydrothermal stability as compared with Fe-Beta (Si/Al = 19), which demonstrates that it is a promising SCR catalyst with good activity as well as hydrothermal stability. The correlation between the quantitative calculation of the content of isolated Fe 3+ in Beta zeolites and the NO conversion rate at 150 °C shows a linear relationship, suggesting that the isolated Fe 3+ species affect the SCR activity directly. The higher activity of the Fe-Beta-9 catalyst is supposed to be related not only to the isolated Fe 3+ but also to the acidity. Furthermore, the template-free synthesized Beta zeolite shows less dealumination during hydrothermal aging and therefore better hydrothermal stability during the SCR reaction.